Breeding Habitat Preference of Aedes aegypti (Linnaeus, 1762) and Aedes albopictus (Skuse, 1895) along an Altitudinal Gradient in Mid-Western Nepal - Oli, Buddhi Ram; Sharma, Manoj; Shrestha, Pramod; Dhimal, Meghnath; Gautam, Ishan (Journal of Institute of Science and Technology, 2024)
Aedes aegypti and Aedes albopictus are vectors of many viral diseases including dengue. They prefer different types of wet containers for breeding which differ according to season and region. Hence, their distribution range and preferred breeding containers should be known for their control. To fulfill the information gap, an intensive survey of potential larval breeding sites was conducted in different altitudinal gradients of mid-western Nepal. A total of 2056 wet containers of 11 different types in 1540 household’s premises were inspected. Among them, 3.35% (n=69) containers of eight different types were positive for larvae and/or pupae of A. aegypti whereas 11 types of total 6.32 % (n=130) wet containers were positive for larvae and/or pupae of A. albopictus. Discarded tires and earthen pots were the most preferred breeding containers for A. aegypti and A. albopictus although the habitat preference was found to be different in different altitudinal gradients and seasons. The proportion of different types of available wet containers and the Aedes infested containers varied across the study sites and seasons. The dengue vectors show their presence up to 2438 m above sea level increasing the risk of Aedes borne diseases up to the high mountain region of mid-western Nepal. Hence, the extensive vector survey and change in breeding habitats either through public health education or by some form of law enforcement is essential.